The Economical Analysis Of Mechanization In Land Preparation For Plantation - M.C. Tri Atmodjo (Bandar Lampung University, 2015)
One of the development of technology in agricultural engineering is the farm mechanization by using farm tractor equipped with disc plow and ridger for land preparation of the plantation. The choose of agrticultural machinery should consider the technical and economical value and the culture of the farmer themselves. The economical analysis shows that One tractor 70 HP and the new price about 800 million rupiah should cultivate 1007hectars of land for a year which 5 years operation until obsolete. The true analysis of technical and economical in the application of farm machinery would increase the total revenue and benefit of plantation.